Using Interactive Power Point Media to Improve The Learning Outcomes of Class V Students - Riska Anastiara Sari (Universitas Sebelas Maret, 2020)
The purpose of this study to improve the learning outcomes of class V students using interactive Power Point media. Classroom Action Research (CAR) is carried out in three cycles, where each cycle consists of planning, implementing, observing and reflecting. The subjects of this study were students of grade V SD Negeri Randuacir 03 for the 2020/2021 school year, totaling 18 students. The techniques collection data use observation and tests. From the results of this study indicate that the use of interactive Power Point learning media can improve student learning outcomes in Theme 5 Ecosystem Content of Indonesian Language Learning as evidenced by the percentage of completeness of learning outcomes in cycle 1 67% to 78% in cycle II and increases again to 83% in cycle III.